(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2019)
This paper analyses the recent sports policies of Florianopolis. This is an exploratory research with analysis of the legal provisions about organization, structure and operation of these policies between 1986 and 2015. It presents three sections according to the different periods and to the content of the documents and the institution of the Sports Municipal Foundation. Scenarios of intense political debate were observed. The legal mechanisms, even the most democratic, were not able to carry higher equity evaluative sport and leisure in all its dimensions. The actions of strengthening the sport "amateur" perpetuate themselves.